Path Planning Based on Visibility Graph with Circular Obstacles for RoboCup Small Size League - Maximo, Marcos R. O. A.; Silva, Artur D. Ferreira da; Neves, Lucas G.; Hirata, Celso M. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
The RoboCup Small Size League (SSL) demands fast and efficient path planning due to its dynamic and competitive environment. While sampling-based techniques have been widely adopted, they often suffer from inconsistencies between replans. In this work, we propose using a path planning approach based on a visibility graph with circular obstacles in SSL. To ensure real-time performance, we implement a lazy graph construction strategy and extensively optimize the code to reduce computational overhead. The shortest path is computed using the A* algorithm. Experimental results demonstrate that our method provides smooth, high-performance trajectories suitable for SSL gameplay.